AN ANALYSIS OF LOCAL GUIDE’S SPEECH ACTS IN GUIDING ACTIVITIES AT CANDIREJO ECOTOURISM VILLAGE BOROBUDUR - Mahardhika Bella Citra A.; Antonius Yuwono; Rini Estiyowati Ikaningrum (Faculty of Education and Teachers Training, 2018)
English is a foreign language that connects people in the whole world. A guide has big role in tourism industry. He should be able to communicate using English because the majority of visitors to the temple are foreign tourists who speak English. The tourist do not understand the illocutionary acts performed by the guide in the form of directive, commissive, representative, expressive, or declarative. Furthermore, misunderstandings or misinterpretations occurs in the communication between the guides and the tourists. The objectives of this research are to analyze the types of illocutionary acts and to find the most dominant type that are found in guide’s utterances in delivering information. In conducting this research the writer recorded the guide’s utterances during guiding activities. The writer transcribed the data and analyzed them to find the types of illocutionary acts using Searle’s classification of illocutionary acts. The writer concluded that there are 5 types of illocutionary acts in the local guide’s utterances, they are directives, commissive, representative, expressive and declarative.